PkM Peningkatan Produksi Bawang Goreng di UMKM SLB Samala Nerugrasha 1 Kunir Lumajang - Siti Zahro; Hany Mustikasari; Yayon Pamula Mukti (GUYUB: Journal of Community Engagement, 2023)
SLB Samala Nerugrasa 1 Kunir opened a small business as a learning place for students with special needs or disabilities who are not easy to get a job directly. However, the production process and knowledge management are not yet optimal. Thus, the aim of the program is to increase fried onion production through training and mentoring as well as updating technologies in these small businesses. The method uses the ABCD approach with five stages. The results of the first phase found that this SLB has assets in the form of complete fried onion production equipment but the condition of the equipment is still manual. The second stage found that his hopes and wishes were that fried onions could be produced every day and the income from selling fried onions was to improve learning facilities at SLB Samala in urder to the graduates will be easy to find jobs after graduated. The third stage, teachers in special schools are encouraged to participate in all activities so that they can impart their knowledge to other teachers and students. The fourth stage, the training carried out was MSME management, food preservation, packaging, and technology renewal. The final stage is that the training is carried out directly and indirectly. Finally, the SLB Samala began to be able to organize his business management and his products were better known for their quality.